Linear Study of Ferromagnetic Convection in Nanofluids Under the Effect of Variable Viscosity - Rajashree, S.; Chandrashekara, N. P. (Communications in Mathematics and Applications, 2023)
Rayleigh-Bénard ferroconvective problem is considered in a Newtonian nanofluid with Fe\({}_{3}\)O\({}_{4}\)-magnetite, as a nanoparticle dispersed in the medium, under the effect of variable viscosity.\ Employing double fourier series, we arrive at the system of differential equations well known as generalized Lorenz Model both in linear and non-linear forms. In the current paper, linear stabillity analysis is considered and graphs have been plotted for stationary nanofluid Rayleigh number \((R_{nfs})\) versus variable viscosity and wavenumber for variant values of buoyancy, non-buoyancy magnetization parameters (BMP and NBMP, respectively) and variable viscosity, and the same has been discussed in detail.
Keywords: Convection; Ferromagnetic nanoliquid; Variable viscosity; Lorenz model